Back to the Future : art contemporain du Moyen-Orient et expositions temporaires au British Museum - Abdallah, Monia (Muséologies, 2018)
The confrontation between contemporary and ancient art, within the framework of temporary exhibitions or in the context of permanent collections, is not new, and examples are numerous. This article shows, through a description of a variety of temporary exhibitions organized by the British Museum, bringing together contemporary Middle Eastern and ancient Islamic art, the ideological consequences of such juxtapositions which consistently favour continuity over rift.